2021
DOI: 10.3897/jucs.66330
|View full text |Cite
|
Sign up to set email alerts
|

Regular Expressions with Lookahead

Abstract: This paper investigates regular expressions which in addition to the standard operators of union, concatenation, and Kleene star, have lookaheads. We show how to translate regular expressions with lookaheads (REwLA) to equivalent Boolean automata having at most 3 states more than the length of the REwLA. We also investigate the state complexity when translating REwLA to equivalent deterministic finite automata (DFA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Additionally, the diagram below summarizes the results of the hierarchy of the language classes. Here, L L denotes the class of languages matched by regular expressions with (both positive and negative) lookaheads, which is known to be equivalent in expressive power to the set of regular languages [4], [5]. From Theorems 1 and 2, we also obtain the following result.…”
Section: Theorem 2 L Bl Is Closed Under Union Intersection and Comple...mentioning
confidence: 96%
See 2 more Smart Citations
“…Additionally, the diagram below summarizes the results of the hierarchy of the language classes. Here, L L denotes the class of languages matched by regular expressions with (both positive and negative) lookaheads, which is known to be equivalent in expressive power to the set of regular languages [4], [5]. From Theorems 1 and 2, we also obtain the following result.…”
Section: Theorem 2 L Bl Is Closed Under Union Intersection and Comple...mentioning
confidence: 96%
“…Previous works on formal language theory have studied the two features mostly in isolation. Morihata [4] and Berglund et al [5] showed that extending regular ex-pressions by lookaheads does not enhance their expressive power. Their proofs are by a translation to boolean finite automata [6] whose expressive power is regular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation